2012
DOI: 10.1093/beheco/ars116
|View full text |Cite
|
Sign up to set email alerts
|

The effects of genotype, caste, and age on foraging performance in leaf-cutting ants

Abstract: The evolution of polyandry is a general problem in behavioral ecology that has attracted particular interest in the social insects. Most social insects are monandrous (i.e., females are inseminated by a single male), but approximately a third of species have evolved polyandry (i.e., females are inseminated by multiple males), which can reach extreme levels. One of the leading explanations for polyandry is that genetically diverse colonies may have improved division of labor because of genotypic variation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…Later studies also showed that workers produced by different fathers in honeybee colonies differ in their likelihood of foraging for pollen or nectar, scouting new nest sites, grooming nestmates, guarding the nest, and removing corpses from the colony (16,45,46). Similar differences among patrilines (or matrilines when colonies contain several queens) were reported in many other species of ants (30,42), bees (16), wasps (113), and termites (62).…”
Section: Worker Polyethismmentioning
confidence: 77%
“…Later studies also showed that workers produced by different fathers in honeybee colonies differ in their likelihood of foraging for pollen or nectar, scouting new nest sites, grooming nestmates, guarding the nest, and removing corpses from the colony (16,45,46). Similar differences among patrilines (or matrilines when colonies contain several queens) were reported in many other species of ants (30,42), bees (16), wasps (113), and termites (62).…”
Section: Worker Polyethismmentioning
confidence: 77%
“…; Constant et al. ) or disease resistance (Hughes and Boomsma , ; Hughes et al. ), and such benefits would only be maximized if sperm was completely mixed after storage.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies, however, have attempted to track labor throughout the worker lifespan in ants (Lenoir 1979; Porter and Jorgensen 1981; Schmid-Hempel and Schmid-Hempel 1984; Kwapich and Tschinkel 2013) or measure age-specific task efficiencies (Muscedere et al 2009, 2013; Robinson et al 2009; Amador-Vargas 2012; Constant et al 2012). Recent studies on the completely dimorphic Pheidole dentata indicate that newly eclosed workers are not behaviorally mature and that age-related myological, neuroanatomical, and neurochemical changes underscore the ability of workers to labor productively (Muscedere et al 2009, 2011, 2012).…”
Section: Worker Longevity and Colony Fitnessmentioning
confidence: 99%